DIGITAL TECHNOLOGY-BASED LANGUAGE LABORATORY MANAGEMENT STRATEGY TO IMPROVE THE QUALITY OF ENGLISH LEARNING AT MTS MUHAMMADIYAH 1 PALEMBANG - Azizah, Deci Fauziah; Berlian, Zainal; Afgani, Muhammad Win (Jurnal Konseling Pendidikan Islam, 2025)
This study aims to observe how the planning strategy for language laboratory management by utilizing digital technology-based media in improving the quality of students' English learning carried out at MTs Muhammadiyah 1 Palembang, and to analyze the principal's organizing strategy in improving the quality of English learning for students at MTs Muhammadiyah 1 Palembang. This research is a qualitative descriptive research. Data collection techniques use observation, interviews, and documentation. Data analysis techniques are used by writing or adopting, editing, clarifying, reducing, and then continuing with the presentation. The results showed that the management of the language laboratory at MTs Muhammadiyah 1 Palembang required 1) a planning strategy, which includes concrete steps to ensure the successful integration of digital technology in learning; 2) organizing, which involves grouping responsibilities according to the functions and duties of each manager. The organization's strategy includes digital technology training for English teachers, hardware maintenance by laboratory personnel, and a well-distributed laboratory usage schedule; and 3) evaluation in the management of the Language laboratory so that learning activities can run well. The organization's strategy includes 1) digital technology training for English teachers, 2) hardware maintenance by laboratory personnel, and 3) a well-distributed laboratory usage schedule.